Para onde vamos? A crise climática e a transição societal em debate na França - Gendron, Janice C. Cavalcanti (2018)
The present thesis provides an analysis related to the civil and political initiatives facing the current climate crisis and the ecological and social consequences. The study focuses on understanding the emerging movement known as “social and ecological transition” that has been under development within the civil society as well as within the French political governmental context. This movement relies on scientific data and opinions of environmental experts as well as on empirical data for analysis of climate change due to anthropogenic impacts in the last two centuries. The empirical research aimed to record and improve the knowledge regarding the actions, profile and speech of activists of the “transition” through an immersion in a local French movement known as “Alternatiba” that has its headquarters in Nantes, France. Methodological instruments that combined on-site observations, semistructured interviews, literature overview and documental research (e.g. internal documents, emails and social media) were employed for a qualitative and comprehensive approach. Some questions were raised during this process, including: What are the emerging conditions of these initiatives? How these initiatives are characterized and organized? What is claimed by them? What are the profiles of the activists? What are the challenges and dilemma involved? This study provides a brief overview of the theories and critics of the development as well as the idea of sustainable development and its unsupportive promises that are observed in the “transition” movement. The study later present an analysis of the emerging application of the “transition” terminology within the context of social and environmental problems. The “transition” movement was examined under the concepts of Boaventura de Sousa Santos such as the “emerging sociology” and the “south epistemology”. The hypothesis that this movement is supported by repetitive epistemology which are evident in the alter-globalist movements and thus in the contra-hegemonic actions is raised. The results of this study shows that the “social and ecological transition” movement provides robust solutions for facing the environmental crisis and decreasing the social and environmental impacts. It also engages on the transformation of the hegemonic lifestyle in order to contribute to the social and ecological transition for a more sustainable, harmonic, united and desirable society. One of the main goals of this movement is public engagement for social and environmental justice. It is also showed herein the main strategies for environmental engagement, influences, challenges and restrictions.